2020
DOI: 10.3390/su12103951
|View full text |Cite
|
Sign up to set email alerts
|

Eradication and Control Strategies for Red Imported Fire Ants (Solenopsis invicta) in Taiwan

Abstract: Invasive alien species are one of the major threats to biological diversity, public safety, agriculture, and economics. In recent years, a new wave of the red imported fire ant (RIFA) has been detected in new regions, including Kobe (Japan), Daegu (South Korea), Kaohsiung (Taiwan), and other locations in southeast Asia. Due to the increasing number of invasions, practitioners and scientists are seeking effective strategies to respond to RIFA invasions in Pacific regions, especially in countries that have had n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
(116 reference statements)
0
5
0
Order By: Relevance
“…The control strategies in the plan included a large-scale broadcast of IGR-based bait in the areas invaded by RIFA in combination with strengthened public education, intensive surveillance (or monitoring) in high-risk areas, and strict control of human-assisted dispersal (movement control). However, the strategies for the prevention and control of RIFA were modified for hot spots and high-risk zone treatment owing to budget constraints after 2012 [ 13 ]. This modification accelerated the spread of RIFA southward and northward from Taoyuan City ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The control strategies in the plan included a large-scale broadcast of IGR-based bait in the areas invaded by RIFA in combination with strengthened public education, intensive surveillance (or monitoring) in high-risk areas, and strict control of human-assisted dispersal (movement control). However, the strategies for the prevention and control of RIFA were modified for hot spots and high-risk zone treatment owing to budget constraints after 2012 [ 13 ]. This modification accelerated the spread of RIFA southward and northward from Taoyuan City ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The initial goal of NRIFACC was to eradicate RIFA from Taiwan completely, and the RIFA control practices have been consecutively performed for 16 years in Taiwan. Although the eradication program is still far from being successful, complete eradication has been achieved in Yi-Lan, Taichung, and Chia-Yi counties [ 13 ]. RIFA was also found on Kinmen Island four years ago (2015); however, genetic data suggested that it was derived from China, and not from Taiwan [unpublished results].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…( 2015 ) 7 = Wetterer and Davis ( 2010 ) 8 = Fukano and Soga ( 2019 ) 9 = Liu et al. ( 2020 ) 10 = Wylie et al. ( 2020 ) 11 = Mufti et al.…”
Section: Appendix B – Distribution Of Solenopsis Invictamentioning
confidence: 99%